Stress fracture of the fifth metatarsal in professional soccer players treated with intramedullary fixation: is a return to sports safe? - Zazueta-Arnaud, Carlos Augusto; Gómez-Carlín, Luis; Radillo-Ubando, Luis Felipe; Ramírez-Gómez, Victor Jonathan; Sánchez-Hernández, Elsa Viridiana (Journal of the Foot & Ankle, 2022)
Objective: To evaluate the clinical and functional outcomes of professional soccer players with zone 3 fractures of the fifth metatarsal treated with intramedullary fixation; and to determine a safe return time to sports. Methods: This study included professional Mexican soccer players with fractures in zone 3 of the fifth metatarsal treated with intramedullary fixation. The clinical and functional status were evaluated with the VAS and Foot and Ankle Ability Measure (FAAM-Sp) Sport Subscale Score. Results: Twenty-two professional soccer players (average age: 20.13 ± 2.85 years) were included. The average postoperative follow-up time was 23.54 ± 15.26 months. Fracture consolidation was demonstrated at 12-week follow-up in all 22 (100%) subjects. The FAAM-Sp Sport Subscale Score was 91.45 ± 8.84 postoperatively; the safe time to return to sports was 12.04 ± 2.21 weeks, when normal or close to normal function was observed in 21 (95%) players. Conclusion: A safe return to sports at 12 weeks, at the same performance level demonstrated prior to injury, was achieved in 95% of professional soccer players in this sample. To our knowledge, this is the first study to explicitly define a time for safe return to sports activities that is related to the critical time required to allow fracture union. Level of Evidence III; Therapeutic Studies; Retrospective Cohort Study.